Produksi Dan Perilaku Produsen Dalam Perspektif Ekonomi Islam - humaira humaira (Assyarikah: Journal of Islamic Economic Business, 2023)
Production is an activity carried out by humans in producing a product, both goods and services which are then used by consumers. Production activities in the Islamic perspective as a human effort to improve not only the physical condition of the material, but also morality, as a means to achieve the goal of life as outlined in religion, namely the happiness of the world and the hereafter. Producer behavior is an action of a producer to get the maximum profit possible by using some of the inputs he has. In the conventional economy, producers do not know the boundaries of halal and haram. Meanwhile, a Muslim producer cannot produce anything that is not halal. Muslim producers are not allowed to do harm to themselves or the community with the products they make. This research was conducted using a descriptive method with a qualitative approach. The results of this study indicate that Islamic economics has its own characteristics. Although in some respects there are certain similarities in its mechanism with conventional economics, it is impossible and never possible to compromise.